Dental caries intensity in children from selected preschools in Bialystok and their families’ socioeconomic status - Wasilczuk, Urszula; Marczuk-Kolada, Grażyna; Łuczaj-Cepowicz, Elżbieta; Chorzewska, Ewa; Kuźmiuk, Anna; Obidzińska, Marta (Journal of Stomatology, 2017)
Introduction. Development of early childhood caries (ECC) can be affected by the economic situation and education of the children’s legal guardians. Aim of the study. To assess the intensity of dental caries of primary teeth in preschool-aged children, taking into account their families’ socioeconomic status. Materials and methods. The study included 483 children aged 2.5-6.5 years and their legal guardians. Children underwent a dental examination. Mean dmf and its components were calculated. Mothers and fathers filled out a questionnaire. Respondents subjectively evaluated the family’s material status as: very good, good, sufficient, and bad. Education was classified as higher, secondary, or primary. Statistica 10.0 software (StatSoft Inc., USA) was used for statistical analysis. A level of p<0.05 for the results was considered statistically significant. Results. General caries intensity in children of mothers and fathers with higher education was significantly lower compared with children of parents with secondary education (mothers p<0.005, fathers p<0.0003). Significantly lower mean dmf was found in children from families with a very good economic status compared with children from families with a sufficient status, both in private and state-run preschools. There were significant differences in the number of carious teeth. Significantly more teeth with lesions (3.29) were found in the group of children whose parents assessed the family’s material status as sufficient compared with children from families with a very good (p< 0.005) and good (p<0.041) status. Conclusion. The study results suggest that parents with lower level of education, particularly mothers, and the family’s material status determine the risk of early childhood caries occurrence.